2022
DOI: 10.3390/s22249877
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Stage Deeply Supervised Attention-Based Convolutional Neural Networks for Mandibular Canal Segmentation in CBCT Scans

Abstract: Accurate segmentation of mandibular canals in lower jaws is important in dental implantology. Medical experts manually determine the implant position and dimensions from 3D CT images to avoid damaging the mandibular nerve inside the canal. In this paper, we propose a novel dual-stage deep learning-based scheme for the automatic segmentation of the mandibular canal. In particular, we first enhance the CBCT scans by employing the novel histogram-based dynamic windowing scheme, which improves the visibility of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…This was based on 256 synthetic annotations, 68 actual annotations, and an internal test set of 15 CBCTs, although limited by the use of a single data source. In contrast, Usman et al 24 reported Dice scores of 0.751 and 0.77 on an internal test set of 500 CBCTs from a unique center and on Cipriano et al’s dataset 25 , respectively, employing a development set of 500 densely annotated CBCTs from a single center. While these results are noteworthy, they are in a different range of magnitude compared to our achieved Dice score of 0.843 (range: 0.810-0.856), underscoring the potential superiority of our method.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…This was based on 256 synthetic annotations, 68 actual annotations, and an internal test set of 15 CBCTs, although limited by the use of a single data source. In contrast, Usman et al 24 reported Dice scores of 0.751 and 0.77 on an internal test set of 500 CBCTs from a unique center and on Cipriano et al’s dataset 25 , respectively, employing a development set of 500 densely annotated CBCTs from a single center. While these results are noteworthy, they are in a different range of magnitude compared to our achieved Dice score of 0.843 (range: 0.810-0.856), underscoring the potential superiority of our method.…”
Section: Discussionmentioning
confidence: 93%
“…The literature acknowledges the complexity of IAN segmentation, largely due to considerable inter-observer and intra-observer variability; for instance, Järnstedt et al 14 reported an inter-observer variability of 0.77 mm, benchmarked against a gold standard set by experienced radiologists. Comparative studies like Cipriano et al’s 25 and Usman et al’s 24 used internal test sets with limited diversity, primarily from one or two centers, often overlapping with their development sets. This lack of external validation and diversity in test datasets limits the generalizability of their findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations